First case report of infection caused by Encephalitozoon intestinalis in a domestic cat and a patient with AIDS - Velásquez, Jorge Néstor (2012)
Fil: Velásquez, Jorge Néstor. Hospital Municipal de Infecciosas Dr. Francisco Javier Muñiz; Argentina.